Entrepreneurship as a career among business students and non business students in UMK and UITM (Kota Bharu) - Kanggadevi Murthi, . (2011)
This study was designed to research the factor influences students to choose entrepreneurship as a career among business students and non-business students in UMK and UITM (Kota Bahru). 100 respondents were selected randomly at UMK and UITM Kota Bahru, Kelantan University by randomly to identify the relationship of factor influencing factors such as perceived behavioral control, entrepreneurial self-efficacy and attitude towards choosing entrepreneurship as a career. This research provides information about factors influencing student’s intention to be an entrepreneur and this information was benefit to any interested parties such as the university.